FACTORS AFFECTING CAREER DEVELOPMENT OF EMPLOYEES IN PT. BANK SULUTGO MANADO - Lalawi, Natasya T.; Tulung, Joy E.; Wangke, Shinta Y. C. (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: Every company or organization needs to make sure that every aspect inside the organization is working efficiently and effectively. One of the most determining factors to a success of an organization is the Human Resource Department. That is why it is required for a company to have qualified a good human capital. Qualified human resource is related with career development of the employees inside the organization. Career development can affect the overall organizational performance. The purpose of this research is to determine the factors affecting career development of employees in PT. Bank SulutGO Manado. This study uses quantitative method using questionnaire to obtain data and use purposive sampling as sampling technique with 80 employees of PT. Bank SulutGO as respondents. This study uses factor analysis as an analysis tool. The result indicates that there are 6 new factors formed that affecting the career development, namely: Self-Evaluation, Behavior & Experience, Personal Ability, Superior Influence, Organizational Policy, and Achievements. Based on the result of the study, the recommendation to the company PT. Bank SulutGO including the employees is to really consider about these factors to create efficiency and effectiveness in the organizational process in order to achieve the goals.Â Keywords: career development, human resource